1981
DOI: 10.4141/cjps81-081
|View full text |Cite
|
Sign up to set email alerts
|

INHERITANCE OF CYCLIC HYDROXAMATES IN Zea mays L.

Abstract: Hydroxamic acids have been implicated in the resistance of corn (Zea mays L.) to both fungi and insects. In this study, five selected crosses were used among the four inbreds BxBx, bxbx, B49 and B37 to study inheritance of hydroxamates. Hydroxamate concentration in the parental, F1, F2 and backcross generations for each cross was estimated by a rapid procedure based upon the colorimetric reaction of hydroxamates with FeCl3. Components of variance and estimates of heritability were obtained by the procedures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…General combining ability accounted for 91% of the variation among hybrids in DIMBOA concentration. From the F 2 and backcross data in maize, Dunn et al . (1981 ) found that the production of hydroxamate is controlled monogenetically in the cross bxbx × BxBxm, and polygenetically in the crosses bxbx × B49 and bxbx × B37.…”
Section: Genetics Of Crop Allelopathymentioning
confidence: 99%
“…General combining ability accounted for 91% of the variation among hybrids in DIMBOA concentration. From the F 2 and backcross data in maize, Dunn et al . (1981 ) found that the production of hydroxamate is controlled monogenetically in the cross bxbx × BxBxm, and polygenetically in the crosses bxbx × B49 and bxbx × B37.…”
Section: Genetics Of Crop Allelopathymentioning
confidence: 99%
“…Likely candidate compounds included the hydroxamic acids (e.g., 2,4-dihydroxy-7-methoxy-2H-l,4-benzoxazin-3(4H)-one, DIMBOA) and their benzoxazolinone derivatives. In at least one line of corn, hydroxamic acid concentrations are determined by a single major partially dominant gene Bx; in other inbred lines, however, hydroxamic acid concentrations are inherited quantitatively, with from two to five loci involved (Dunn et al, 1981). Depending on the variety, hydroxamic acid levels can be influenced by environmental conditions, including light intensity, temperature, and iron and nitrogen concentrations (Nie meyer, 1988).…”
Section: Genetically Based Resistance To Herbivores Is Attributabmentioning
confidence: 98%
“…According to Ehrlich and Raven (1964), plant chemistry acts as a major selective agent on insect populations. More than 25 years later, there is little evidence that chemistry per se is accountable for genetically based differences in insect performance on different host plants (and no evi dence of which we are aware that chemistry is accountable for genetically based differences in performance of any other type of herbivore).…”
Section: Intraspecific Differences In Herbivore Performance On Plmentioning
confidence: 99%
See 1 more Smart Citation